(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This article aims to publish [C.18.7], an Iberian inscription on an arula preserved at the Museo Nacional Arqueológico de Tarragona that has been considered lost until now.